Case Report: Lymphocytosis Associated With Fatal Hepatitis in a Thymoma Patient Treated With Anti-PD1: New Insight Into the Immune-Related Storm - Argentiero, Antonella; Solimando, Antonio Giovanni; Ungaro, Valentina; Laforgia, Mariarita; Strippoli, Sabino; Pinto, Dario; Negri, Antonio; Ferraiuolo, Simona; Zito, Alfredo; Guida, Michele (Frontiers in Oncology, 2020)
Recent advances in tumour immunotherapy have made it possible to efficiently unleash immune effectors, reacting against neoplastic cells. Although these approaches primarily aim to eradicate malignancy, immune-related adverse events (irAEs) often influence patients prognosis, constituting a new spectrum of side effects. Taking into account the typical microenvironment and the intricate equilibrium between the anti-tumour response and the immune cells, the thymoma constitutes a unicum in the immune-oncology field. We report a fatal immune-mediated adverse events storm in a thymoma patient treated with Pembrolizumab, leading to hepatotoxicity accompanied by lymphocytosis, thrombocytopenia, and thyroid dysfunction, unveiling a novel potential pathophysiological effect of immunotherapy. The clinical proficiency of the immune checkpoint inhibitors in thymoma patients warrants timely prevention and management of off-target consequences, in order to optimize this promising therapeutic option. This case report describes a unique consequence of irAEs, emerging as a red flag warranting a multidisciplinary approach.